EXPERIMENTAL STUDY AND OPTIMIZATION OF MACHINING PARAMETERS IN MILLING PROCESS OF INCONEL-718 - Eswar Balachandar. G; Sambaturu Gopi. S; V. Mahidhar Reddy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this study was to optimize the end milling of Inconel 718, a hard-to-machine alloy, owing to its nickel content, using Grey Relational Analysis (GRA). The primary goal was to identify and implement the optimal cutting parameters. One of the key parameters investigated was the diameter of the tool and speed of the spindle. The study results reveal that 0.9 mm depth of cut, 1400 rpm spindle speed, and 8 mm tool diameter resulted in significant improvements. Compared to 0.54 cc/min before, the material removal rate (MRR) is much higher from 2.16 to 2.16 cc/min after. The surface roughness (Ra) was approximately 0.742 m, and the material removal rate (MRR) was approximately 0.208 m. There are profound implications for the aerospace and automotive industries, which frequently use Inconel 718. The machining efficiency and product quality can be improved by implementing the identified optimal parameters. GRA can be useful in optimizing Inconel 718 machining in a manner that improves both material removal rates and surface quality, thus demonstrating its feasibility and originality.